Consecutive retrieval of aerosol optical depth and total suspended solid concentration in turbid coastal water of Eastern China. (September 2022) - Tan, Xinyao; Sun, Bingqiang; Wang, Guochen; Cheng, Tiantao; Huang, Kan; Shen, Fang
Highlights: MODIS band 7 (around 2.1 µm) is employed to retrieve the aerosol optical depth (AOD) in turbid coastal water, which fills the gap of satellite aerosol products in coastal water. The retrieved AOD optimizes the atmospheric correction process. MODIS band 4 (around 0.55 µm) is used to establish the retrieval model of total suspended solid (TSS). The AOD and the TSS in turbid coastal water can be consecutively and accurately retrieved using one shortwave infrared band and one visible band. Abstract: An algorithm is proposed for consecutive retrieval of aerosol optical depth (AOD) and total suspended solid (TSS) concentration in turbid coastal water using a shortwave infrared band and a visible band. MODIS band 7 (∼2.1 µm) was used to retrieve the AOD in turbid coastal water, as the top-of-atmosphere reflectance in this band is more sensitive than in other bands and water-leaving reflectance ( ρw ) can be ignored. The aerosol model is determined through iteration by predetermining the proportion range of four basic aerosol modes (dust, water-soluble, ocean and soot). The retrieved AOD is used for atmospheric correction. Based on the Pearson correlation coefficient between TSS and ρw for the different bands, MODIS band 4 was used to obtain ρw . A logarithmic model associated with TSS retrieval was established between ρw and TSS products of GOCI. For the MOD09GA product, the median, moving, adaptive, and Fourier-transform filters were employed to eliminate strip noise with respect to TSS retrieval. The retrieved AOD was strongly correlated with AOD observed at the Huaniao Island site ( R  = 0.94; RMSE = 0.0437; mean absolute percentage error (MAPE) = 10.9%). The new AOD retrievals are more accurate than MODIS ocean retrievals and can provide missing AOD products in turbid coastal areas. Fourier-filtered TSS has the best retrieval results (RMSE = 1.3538; MAPE = 32.03%) in comparisons between retrieved and in situ TSS.